Severe Kala-azar and seric level of IL-6: case reports - Brito, Gilmara da Rocha; Marreiros, Aécio da Silva; Araujo, Izael Francisco de Brito; da Silva Júnior, Raimundo Gerônimo; Sene, Ingridi de Souza; Braz, Débora Cavalcante (Journal of Health & Biological Sciences, 2020)
Introduction: IL-6 cytokine participates in the inflammatory process of systemic leishmaniasis and elevated levels are associated with active disease. Case reports: Three patients with different age groups and different severity scores, above 4 were reported, and IL-6 plasma concentrations and their association with disease severity were observed. Conclusion: Analysis suggests that only the score, has no sensitivity to classify, among others critically ill patients, those with imminent risk of death. IL-6 concentrations can allow this differentiation, considering that only fatal case, HBV/Leishmania coinfection, presented expressively higher level of the cytokine concentration.